The critical success factors of recycling construction waste in Selangor, Malaysia - Nur Amni Halme (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Construction waste is a serious issue in Malaysia due to the negative impact it puts on the environment, economy and society. Hence, this research is carried out to determine the critical success factors of conducting recycling construction waste in Selangor, Malaysia. Three research objectives has been identified which are to review the current status of construction waste recycling in Malaysia, to identify the type of waste frequently generated at construction sites in Selangor, Malaysia and to determine the critical success factors of construction waste recycling in Selangor, Malaysia. A quantitative method involving questionnaire was used as means of data collection. The data were gathered from 30 construction companies including consultant, contractors and developers in Selangor, Malaysia. The analysis found that the construction waste management in Malaysia is ambiguous and requires major revision in term of policy, awareness and practices. This research also found that the types of waste material that frequently generated at construction site are timber, steel, and concrete due to their vast usage in construction activities. Lastly, nine (9) critical success factors (CSFs) for conducting recycling of construction waste have been identified; (CSF1) establish a recycling law for Construction Waste, (CSF2) higher landfill-charging scheme, (CSF3) On-site sorting practice, (CSF4) Contractual provision for recycling construction waste, (CSF5) establish a standard for recycled construction waste, (CSF6) centralized recycling plant, (CSF7) establish a recycling system for construction waste within companies, (CSF8) location of recycling plant and (CFS9) awareness of recycling benefit.